2019
DOI: 10.3390/molecules24203653
|View full text |Cite
|
Sign up to set email alerts
|

Antiglycation Activity of Aucubin In Vitro and in Exogenous Methylglyoxal Injected Rats

Abstract: Advanced glycation end products (AGEs) is a causative factor of various chronic diseases, including chronic kidney disease and atherosclerosis. AGE inhibitors, such as aminoguanidine and pyridoxamine, have the therapeutic activities for reversing the increase in AGEs burden. This study evaluated the inhibitory effects of aucubin on the formation of methylglyoxal (MGO)-modified AGEs in vitro. We also determined the potential activity of aucubin in reducing the AGEs burden in the kidney, blood vessel, heart, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 44 publications
0
2
0
1
Order By: Relevance
“…Согласно первоначальным предположениям, выдвинутым для аналога соединения ALT-711 -фенилтиазолия бромида [16], механизм его действия включает разрыв С-С связи между двумя соседними карбонильными группами. Однако КПГ, содержащие подобный 1,2-дикарбонильный фрагмент, в условиях эксперимента установлены не были, хотя разрыв поперечных сшивок был доказан экспериментально, иммунологически, с применением антител к тому или иному из двух сшитых белков [30][31][32][33]. Следует отметить, что такая С-С связь, расположенная между двумя соседними карбонильными группами, присутствует в некоторых ранних продуктах гликирования [22].…”
Section: Discussionunclassified
“…Согласно первоначальным предположениям, выдвинутым для аналога соединения ALT-711 -фенилтиазолия бромида [16], механизм его действия включает разрыв С-С связи между двумя соседними карбонильными группами. Однако КПГ, содержащие подобный 1,2-дикарбонильный фрагмент, в условиях эксперимента установлены не были, хотя разрыв поперечных сшивок был доказан экспериментально, иммунологически, с применением антител к тому или иному из двух сшитых белков [30][31][32][33]. Следует отметить, что такая С-С связь, расположенная между двумя соседними карбонильными группами, присутствует в некоторых ранних продуктах гликирования [22].…”
Section: Discussionunclassified
“…Examining the antiglycation activity in vitro at concentrations of 0.22 mmol/L and in vivo at 10 and 25 mg/kg revealed that aucubin suppressed the formation of advanced glycation end products (AGEs). This inhibitory effect on the formation of AGEs is dose-dependent [ 79 ]. AGEs are a causative factor for, among others, chronic kidney disease and atherosclerosis.…”
Section: Biological Propertiesmentioning
confidence: 99%
“…In another work, administering oral aucubin at a dose of 15 mg/kg BW prevented retinal degeneration induced using N-methyl-N-nitrosourea in mice. This effect is believed to result from the inhibition of oxidative damage and apoptosis of DNA, as shown by the decrease in 8-OHdG generally formed due to the generation of excess ROS [ 79 ].…”
Section: Biological Propertiesmentioning
confidence: 99%